2019
DOI: 10.1177/2156759x19885888
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy in Action: The Use of Photovoice in School Counseling

Abstract: Photovoice is an innovative approach that uses photography to promote empowerment and social action. Although photovoice has been recognized as a valuable intervention for youth, projects involving this approach primarily have been facilitated by university–school partnerships or community organizations. Aligned with the American School Counselor Association National Model, this article proposes photovoice as a practical tool that school counselors can incorporate into a comprehensive school counseling program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A mix of empirical and conceptual articles ( n = 9) explained how YPAR can be used as a framework for a group counseling process. Of these group-centric papers, a handful ( n = 6) used photovoice to analyze school policies, share untold stories, identify barriers to academic achievement, examine community issues, and/or process race-related stress (Edirmanasinghe, 2020; Edirmanasinghe & Blaginin, 2019; Roxas et al, 2017; Smith et al, 2012; Stickl Haugen et al, 2019; Williams et al, 2020). Photovoice is a YPAR method where youth take and/or curate photos to promote a critical discussion about social issues impacting their community and, by focusing on their community strengths, develop solutions to reach policy makers (Williams et al, 2020).…”
Section: Results: How Can School Counselors Use Ypar Practices and Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…A mix of empirical and conceptual articles ( n = 9) explained how YPAR can be used as a framework for a group counseling process. Of these group-centric papers, a handful ( n = 6) used photovoice to analyze school policies, share untold stories, identify barriers to academic achievement, examine community issues, and/or process race-related stress (Edirmanasinghe, 2020; Edirmanasinghe & Blaginin, 2019; Roxas et al, 2017; Smith et al, 2012; Stickl Haugen et al, 2019; Williams et al, 2020). Photovoice is a YPAR method where youth take and/or curate photos to promote a critical discussion about social issues impacting their community and, by focusing on their community strengths, develop solutions to reach policy makers (Williams et al, 2020).…”
Section: Results: How Can School Counselors Use Ypar Practices and Pa...mentioning
confidence: 99%
“…According to studies considering youth’s college and career development ( n = 4), school counselors can use YPAR to grow college-ready research skills and critical consciousness (Scott et al, 2015), career self-efficacy (Edirmanasinghe & Blaginin, 2019), and leadership skills (Ozer & Wright, 2012), and to explore issues of college access (Cook et al, 2019). Studies tending to students’ academic development ( n = 4) found that school counselors may use YPAR to approach retention issues in mainstream and alternative education (Chou et al, 2015); to assess reading achievement, bolster attendance, and address problematic discipline referral rates (Voight & Velez, 2018); and to support students’ critical thinking (Stickl Haugen et al, 2019) and self-efficacy in STEM (Edirmanasinghe, 2020). Two articles pointed to the use of YPAR to simultaneously promote students’ social/emotional, academic, and/or career (i.e., holistic) development (Hipolito-Delgado et al, 2021, Williams et al, 2020).…”
Section: Results: How Can School Counselors Use Ypar Practices and Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers also used photovoice with Muslim participants to explore their experiences related to different specific topics including physical exercise and women's role (Bromfield and Capous-Desyllas 2017;Chakraborty 2009;Eyres et al 2019;Miled 2019;Murray et al 2015;Reimers 2016;Samsuni et al 2019) and high school students in education (Roxas and Vélez 2019). Similarly, other researchers reported that photovoice enables the acquisition of people's experiences more accurately as they can identify, represent, and enhance their own or their community's status through captions, explanations, and photos (Davtyan et al 2016;Haugen et al 2019;Nitzinger et al 2019;Strack et al 2015;Sullivan 2017). Wang and Burris (1997) developed photovoice to empower women with few opportunities living in a rural area; therefore, it makes sense that they conducted their study with a few women, faceto-face, and in small groups.…”
mentioning
confidence: 99%
“…However, school counselors should still clearly explain confidentiality and others' right to privacy with their participants. School counselors should have a clear protocol for students who want to take photographs of other students or other people (Stickl Haugen et al, 2019).…”
Section: Considerations For Implementationmentioning
confidence: 99%